From the house to the plaza? Agency and politicization in the trajectories of Adelina Dematti and Aída Bogo before joining the Mothers of Plaza de Mayo (2021)
The objective of this work is to reflect upon the trajectories and experiences of political participation of the women who were part of the Mothers of Plaza de Mayo movement, focusing on the period prior to their incorporation into the organization, based on the cases of two of their members: Adelina Dematti and Aída Bogo. Their experiences of participation in different areas of the public sphere were recovered and the politicization of their trajectories linked to the private spheres and the world of labor were analyzed. How they narrate the experience of their incorporation into the organization was identified. This approach will help to highlight that even when these women have been recognized as central agents and protagonists of the resistance to the dictatorship, their trajectories of prior political participation were invisibilized. It will also give account of the political dimensions of the spheres socially denominated as «private». A qualitative approach was adopted to enquire intothe meanings that both women built around the events they went through, based on carrying out and analyzing interviews. The Adelina Dematti de Alaye Documental fund, a member of the Mothers of Plaza de Mayo-La Plata, was also consulted.